If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -8x = 48 + -22x Solving 12 + -8x = 48 + -22x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22x' to each side of the equation. 12 + -8x + 22x = 48 + -22x + 22x Combine like terms: -8x + 22x = 14x 12 + 14x = 48 + -22x + 22x Combine like terms: -22x + 22x = 0 12 + 14x = 48 + 0 12 + 14x = 48 Add '-12' to each side of the equation. 12 + -12 + 14x = 48 + -12 Combine like terms: 12 + -12 = 0 0 + 14x = 48 + -12 14x = 48 + -12 Combine like terms: 48 + -12 = 36 14x = 36 Divide each side by '14'. x = 2.571428571 Simplifying x = 2.571428571
| y=x^2+3x+1 | | 10+4x=22 | | 6x^2=39x-45 | | 0=x^2(x^4+6x^2-16) | | 12x+24=8x+4 | | -2x-13=x+2 | | -2-13=x+2 | | 6-10x=66-45x | | -x^2+18x+19=0 | | 2x+6=x+1 | | 5x+10y= | | ln(3x)+ln(5)=2 | | 2x-2=x+6 | | 7x+22=5x+50 | | 6-10x=46-24X | | 5x^2+26x+24= | | 4n-5=27 | | -3x-4=x+24 | | 5a-40=a | | 10x-118=4x-10 | | -2(3x)= | | 3x+19=2x | | x-9=4x+3 | | x-9=-6 | | 4y=9y-20 | | x+-12=4 | | (-3g)-3=5+g | | 12x+9=6x+11 | | 32x=-64 | | 6v(2v+3)= | | 11n+5=6n | | 127-4=4x+4 |